Kepentingan pendidikan patriotisme terhadap warganegara Malaysia - Ku Samsu, Ku Hasnita; Mohd Nor, Mohd Haizam (Department of Southeast Asian Studies, Faculty of Arts and Social Sciences, University of Malaya, 2011)
A sense of "patriotism" is not present by itself in human life, but this feeling has to be propagated, fertilized and nurtured to be, fresh and powerful in the soul of each and every citizen. Thus, the process is linked to continuous patriotic education within formal or informal contexts. Patriotic education, formally, involves planned and systematic learning activities, includes schools' syllabus, universities' compulsory courses, and the National Service Training Program (PLKN). On the other hand, informal patriotic education which involves haphazardly unplanned activities could occur by chance throughout human life. This type of education may begin as early as infancy. Hence, patriotic education has a very broad scope across the life experience and, is significant over time. Accordingly, this paper will examine the importance of patriotic education upon the citizens of Malaysia in facing challenges that could erode their identity as Malaysian.